A lethal form of gorham disease associated with extensive musculoskeletal pneumatosis: cse report and review of the literature (2008)
We report here the imaging finding of a rare case of a lethal form of gorham disease in a yound female patient. Multimodality imaging findings over 13 years- follow-up demostrated progressive wide spread skeletal and soft tissue abnormalities with permeative osteolysis, pathological fractures and severe sketal deformities. Unusual extensive osseous and soft tissue pneumatosis was illustrated on cross-sectional studies. The progressive nature of this form of gorham disease and the subsequent complications eventually culminated in patients's death.